2009
DOI: 10.1007/s12206-009-0334-3
|View full text |Cite
|
Sign up to set email alerts
|

A study on the modeling and analysis of a helicopter’s occupant seat belt for crashworthiness

Abstract: In this paper, a method of modeling a seat belt on a crew seat during a dynamic seat testing was studied. The body segments of the occupant were modeled with joints that consisted of various stiffness, damping, and friction. Three types of seat belt restraint systems were investigated and an analysis on the injury assessment of the helicopter's crew under a drop impact was conducted. The effectiveness of the seat belt system for crashworthiness and safety was likewise evaluated. From the impact analysis result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…The dynamic response of a seat belt restraint system also has important influences on the safety of occupants. The effectiveness of a seat belt system must be strictly evaluated during the crashworthiness design [191]. Besides, the search for the feasible region is a useful method to determine the portion of the domain where design variables can be adjusted to satisfy the requirements of performance and regulations.…”
Section: Helicopter Seatsmentioning
confidence: 99%
“…The dynamic response of a seat belt restraint system also has important influences on the safety of occupants. The effectiveness of a seat belt system must be strictly evaluated during the crashworthiness design [191]. Besides, the search for the feasible region is a useful method to determine the portion of the domain where design variables can be adjusted to satisfy the requirements of performance and regulations.…”
Section: Helicopter Seatsmentioning
confidence: 99%
“…Although crash-resistant fuel systems in civil helicopters may not be as effective as those used in military helicopters, Hayden et al (2005) showed effectiveness in prevention of post-crash fires and thermal fatalities. Findings from additional research on fuel systems, crash-resistance, seats, and restraints used in military helicopters formed the basis for development and evaluation of criteria for civil helicopters (Jackson 2018;Lee et al 2009;Desjardins 2006;Robertson et al 2002;Coltman 1994;Coltman et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Although crash-resistant fuel systems in civil helicopters may not be as effective as those used in military helicopters, Hayden et al (2005) showed effectiveness in prevention of post-crash res and thermal fatalities. Findings from additional research on fuel systems, crashresistance, seats, and restraints used in military helicopters formed the basis for development and evaluation of criteria for civil helicopters (Jackson 2018;Lee 2009;Desjardins 2003;Robertson et al 2002;Coltman 1994;Coltman et al 1985).…”
Section: Introductionmentioning
confidence: 99%